(untitled) (Journal of Engineering, 2015)
Experimental research was carried out to investigate the performance of CFRP wrapping jackets used for retrofitting twelve square reinforced concrete (CR) column specimens damaged by exposure to fire flame, at different temperatures of 300, 500 and 700ºC, except for two specimens that were not burned. The specimens were then loaded axially till failure after gradual or sudden cooling. The specimens were divided into two groups containing two main reinforcement ratios, ρ= 0.0314 and ρ= 0.0542. This was followed by the retrofitting procedure that included wrapping all the specimens with two layers of CFRP fabric sheets. The test results of the retrofitted specimens showed that the fire damaged RC column specimens can be retrofitted efficiently by using CFRP wrap jackets, as they provided good confinement of the damaged concrete core. Also, the ultimate load capacity of each retrofitted specimen was increased compared to that before retrofitting by about 16, 34 and 44% for the specimens burned at 300, 500 and 700ºC respectively, and cooled gradually, whereas this increase was 44% and 111% for the specimens subjected to burning temperatures of 500 and 700ºC, respectively, but cooled suddenly. This ability of each column specimen to absorb energy before and after retrofitting was also improved. The average improvement in modulus of toughness before and after retrofitting was 8% for the specimens not exposed to fire flame and 10, 100, 250% for the specimens exposed to 300, 500 and 700ºC respectively.